(untitled) (New York, 1991)
In "American History: A Survey", Alan Brinkley manages to create a comprehensive survey of American history, devoting in-depth discussion to both political and social history. In the process new insight is shed on familiar events while important aspects of the past which tend to be overlooked, e.g. Native Americans, women and African Americans, are covered in detail.
Keywords: United states; History